Divorced wife’s right to maintenance under Islamic and civil law: possibility of harmonisation - Mohd, Azizah; Abd Malek, Normi; Hj Ibrahim, Badruddin; Mohd Najid, Khadijah (2021)
The relationship between husband and wife creates certain rights and obligations that both of them are to enjoy and fulfill especially during the subsistence of marital relationship. Both Islamic and Civil law are in agreement that maintenance is one of the rights of the wife and one of the obligations of the husband. The right continues even after the wife is divorced but is subject to certain conditions and limitations under which the two laws differ. This paper seeks to examine especially the point of differences on the divorced wife's right to maintenance under both the Islamic and Civil Laws. The paper aims to critically investigate whether the Civil law on the right of a divorced wife to maintenance can be harmonized with Islamic law. For that purpose, the discussion will include the provisions of divorced wife rights to maintenance under Islamic law (the Shari’ah) as well as the provisions of the law that governs the Muslims in Malaysia. The discussion extends to the provision of Civil law that governs the non-Muslims particularly the Married Women and Children (Maintenance) Act (1950) and the Law Reform (Marriage and Divorce) Act 1976. The research adopts a qualitative methodology whereby analysis will be made based on materials in Library and statutes. Finally, this paper will provide suggestions on harmonization of Islamic and Civil law where relevant and possible.